Failure of AAV retrograde tracer transduction in hypothalamic projections to the periaqueductal gray matter - João Guilherme Tassoni Bortoloci; Simone Cristina Motta (Heliyon, 2022)
Connectomics is an important field of neuroscience that examines how neurons are connected and form functional circuits that underly the brain's functions. Conventional tracers based on dye have led to great advances in mapping these connections, and now, neurotropic viruses are contributing to connectomics. In this work, two retrograde adeno-associated virus failed to transduce in projections from hypothalamic neurons to periaqueductal gray matter (PAG) but worked well in cortical connections to PAG. One of this virus also marked a substantial amount of PAG efferent projections, therefore working as an anterograde tracer. We also used hydroxystilbamidine (FluoroGold™) as a gold standard in retrograde tracing for comparison with the projections shown by the retrograde virus. As determined in past works, FluoroGold™ shows connections from the hypothalamus and cortex to the PAG. Also, an anterograde AAV was compared with one of the retrograde AAV, which showed a similar pattern of axonal projections and terminal fields. Hence, although neurotropic viruses are revolutionizing connectomics and other areas, their mechanism, neurotropism, and cell invasion need to be addressed. Their use is a great challenge and requires further studies to clarify their interaction with the nervous system's cells.